Tourism Village Marketing Branding Towards Sustainable Tourism Based on Local Wisdom - Surya, Elfitra Desy; Mesra, Mesra; Kadir, Zahidah Abd (Jurnal Manajemen Bisnis, 2024)
Research aims: This study aims to test and analyze the influence of tourism village branding marketing towards sustainable tourism based on local wisdom.Design/Methodology/Approach: This study employs a quantitative methodology with an associative approach. The study population comprises travelers who visit the Hutatinggi tourist village in the Lake Toba superpriority area which totals 980 tourists. The sample in this study amounted to 140 tourists obtained from 7 x the number of indicators, where the number of Indians was 20x7 = 140 tourists.Research findings: The study's findings indicate, it was found that the variables brand experience, perceived value, brand loyalty, and brand love exert a beneficial and substantial impact on the promotion and maintenance of sustainable tourism. The variables of brand experience, perceived value, brand loyalty, and brand love have a positive and significant influence on sustainable tourism through satisfaction.Theoretical Contribution/Originality: The variables of brand experience, perceived value, brand loyalty, and brand love have a positive and significant influence on sustainable tourism through satisfaction.Practitioners/Policy Implications: The limitations of this research are only for tourist villages in the Lake Toba area, and in the future, it can be developed to tourist villages throughout Indonesia. Research Limitations/Implications: The contribution of local wisdom to be able to increase sustainable tourism for marketing and branding of tourist villages in Hutatinggi, Toba Samosir.